CDK12 and HER2 coamplification in two urothelial carcinomas with rapid and aggressive clinical progression. Issue 12 (23rd October 2020) - Yanai, Yoshinori; Kosaka, Takeo; Nakamura, Kohei; Aimono, Eriko; Matsumoto, Kazuhiro; Morita, Shinya; Mikami, Shuji; Nishihara, Hiroshi; Oya, Mototsugu
Abstract: Cyclin‐dependent kinase 12 ( CDK12 ), one of the key factors associated with DNA damage response pathways, is located on chromosome 17 proximal to Erb‐B2 receptor tyrosine kinase 2 ( ERBB2 ). In this report, CDK12 and ERBB2 coamplification was detected by targeted next‐generation sequencing in two urothelial carcinomas. The staining intensity of the CDK12 and human epidermal growth factor receptor‐2 proteins was associated with the prognosis of each urothelial carcinoma case. Our results suggest that CDK12 coamplification with ERBB2 might be associated with tumor aggressiveness and contribution to cancer pathogenesis. Therapies targeting CDK12 should be developed for these patients.